Kinetic Parameters and Structural Variations in Cu-Al-Mn and Cu-Al-Mn-Mg Shape Memory Alloys - Aksu Canbay, Canan (Amer Inst Physics, 2017)
In this work polycrystalline Cu-Al-Mn and Cu-Al-Mn-Mg SMAs were fabricated by arc inciting. The thermal analysis was made to determine the characteristic transformation temperatures of the samples and kinetic parameters. Also the effect of Mg on transformation temperatures and kinetic parameters detected. The structural analysis was made to designate the diffraction planes of martensite phase at room temperature and this was supported by optical measurement observations.
32nd International Physics Congress of Turkish-Physical-Society (TPS) -- SEP 06-09, 2016 -- Bodrum, TURKEY
Keywords: Martensitic-Transformation; Phase; Microstructure; Manganese